2015
DOI: 10.1016/j.parint.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Tandem repeat recombinant proteins as potential antigens for the sero-diagnosis of Schistosoma mansoni infection

Abstract: The diagnosis of schistosome infection, followed by effective treatment and/or mass drug administration, is crucial to reduce the disease burden. Suitable diagnostic tests and field-applicable tools are required to sustain schistosomiasis control programs. We therefore assessed the potential of tandem repeat (TR) proteins for serodiagnosis of Schistosoma mansoni infection using an experimental mouse model. TR genes in the genome of S. mansoni were searched in silico and 7 candidates, named SmTR1, 3, 8, 9, 10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Recombinant antigen ELISAs have potential to increase the specificity of assays [74-77]. In our study, rMEA-IgG-ELISA showed sensitivity of 87.10% and specificity of 89.09% represented by AUC = 0.95.…”
Section: Discussionmentioning
confidence: 51%
“…Recombinant antigen ELISAs have potential to increase the specificity of assays [74-77]. In our study, rMEA-IgG-ELISA showed sensitivity of 87.10% and specificity of 89.09% represented by AUC = 0.95.…”
Section: Discussionmentioning
confidence: 51%
“…ELISAs were performed with different recombinant S. mansoni antigens as described elsewhere [21,34], including sm31, sm32, RP26, serpin, filamin, tropomyosin, GST, LAP1, and LAP2. The SWAP and SEA crude antigens were also compared with the recombinant antigens of interest.…”
Section: Enzyme-linked Immunosorbent Assays (Elisas) Of Serum Antibodiesmentioning
confidence: 99%
“…The human CFH (PDB entry 3GAW) contains sushi/ccp domain repeats ( Fig 5C) involved in regulating complement cascade. Smp_182770 does not contain the sushi/ccp domain repeats but it does encode tandem repeats similar to those expected from mammalian CFH genes [70].…”
Section: Discussionmentioning
confidence: 96%